Optimasi Kecepatan dan Lama Pengadukan dalam Preparasi Microspheres Metformin Hidroklorida Menggunakan Polimer Etil Selulosa (Optimization of Stirring Speed and Time on Preparation of Metformin Hydrochloride Microspheres Using Ethyl Cellulose Polymer) - Amalia Fadila; Lusia Oktora Ruma Kumala Sari; Eka Deddy Irawan (Pustaka Kesehatan, 2016)
Metformin hydrochloride (MH) is a first line therapy in the treatment of noninsulin-dependent diabetes mellitus. However, MH has a very short half-life, relatively low bioavailability, and gastrointestinal adverse effects. Controlled released formulations can overcome this problem by increasing gastro retention time (GRT). Drug delivery systems aimed at improving GRT can be designed in a single units (eg, tablets) and multiple unit (eg, microspheres). Stirring speed and time affect several aspects such as shape, size, and particle size distribution, the release rate, and entrapment efficiency (EE) of the microspheres.. This research was aimed to find the stirring speed and time to produce MH microspheres having high EE. The result showed that the microspheres stirred at 1,000 rpm for 2 hours produced the highest EE, 84.792 ± 0.975 %; had the drug loading of 12.067 ± 0.0649 %; and yield of 99.44 ± 0.123 % with the particle size 157.5 ± 1.007 μm, has the spheres shape and a relatively smooth and bright surface morphology. FTIR analysis results indicated that there were no changes in the functional groups on MH as an active ingredient. Keywords: metformin hydrochloride-ethyl cellulose microspheres, non-aquoeous solvent evaporation, stirring speed, stirring time, factorial design